PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH POWTOON BERBASIS INQUIRY LEARNING UNTUK MENINGKATKAN CRITICAL THINKING SKILLS DENGAN MENGGUNAKAN MODEL ASSURE - Puji Rizki Irani; Sumardi Sumardi; Nurul Umamah (Universitas Sultan Ageng Tirtayasa, 2022)
Abstract: The paradigm of independent learning and the development of digital technology have brought major changes in the historical learning. Educators are required to innovate in learning in order to develop students' critical thinking skills (CTS). However, the results of previous studies and preliminary observations showed problems related to the low CTS of students. The purpose of this research and development is to provide an alternative solution to the low CTS of students by developing a media powtoon based on inquiry learning. The design uses the ASSURE development model stages. The result of research and development is powtoon media based on inquiry learning, which is validated by experts and can improve CTS. The results of the validation of content experts in the field of study reached 94% with